2011
DOI: 10.1245/s10434-010-1536-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Volume Increase During Preoperative Chemotherapy as a Novel Predictor of Local Recurrence in Extremity Osteosarcoma

Abstract: A TVR increase during preoperative chemotherapy could be used to predict patients at high risk of LR. This finding might be useful when considering surgical options to decrease the risk of LR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Tumor volumes after treatment were divided by volumes before chemotherapy and are expressed as tumor-volume-reduction ratios (TVRs). 10 During the exponential growth phase, the tumor-volume-doubling time (Td) was calculated using the following formula 11 : Td = t × [log 2/(log Vb -log Va)], where Va is tumor volume at initial and Vb that at t days after Va.…”
Section: Tumor Model and Experiments Protocolmentioning
confidence: 99%
“…Tumor volumes after treatment were divided by volumes before chemotherapy and are expressed as tumor-volume-reduction ratios (TVRs). 10 During the exponential growth phase, the tumor-volume-doubling time (Td) was calculated using the following formula 11 : Td = t × [log 2/(log Vb -log Va)], where Va is tumor volume at initial and Vb that at t days after Va.…”
Section: Tumor Model and Experiments Protocolmentioning
confidence: 99%
“…Recently, we reported that an increase in tumor volume (TV) during preoperative chemotherapy is related with poor histologic responses and it also is a novel predictor of LR in extremity osteosarcoma 9). Furthermore, subsequently performed cohort and case-control survival analysis between patients with LR and without LR suggested that LR has only a small effect on survivals among patients showing resistance to chemotherapy 10).…”
mentioning
confidence: 99%
“…In a recent study, Song et al . showed that increase in tumor volume during preoperative chemotherapy is a prognostic factor for LR in osteosarcomas 9. However, they also mentioned that poor response to preoperative chemotherapy could also be a reason in their study for higher local relapses in patients with high tumor volume since chemotherapy response is an important prognosticator for local recurrence.…”
Section: Discussionmentioning
confidence: 94%
“…With the same premise, we can conclude that the high volume of initial tumor will also affect the LR rates in osteosarcomas. Studies evaluating high tumor volume as a prognosticator for LR in patients undergoing limb salvage surgeries are few and with conflicting results 789…”
Section: Introductionmentioning
confidence: 99%